PENGARUH KONSERVATISME, LEVERAGE, PROFITABILITAS, UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE - Camelia Mayang Susanti (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2018)
The objective of this study is to examine the effect of Accounting Conservatism, Leverage, Size, Capital Intensity Ratio, Inventory Intensity Ratio, and Profitability Against Tax Avoidance. The population of this study is Manufatur Company listed on the Indonesia Stock Exchange in 2013-2017. The sampling method used is Purposive sampling method and the sample of this study is 121 sample. The data collection is conducted by www.idx.co.id .The results showed that the variables of Accounting Conservatism, Leverage, Size, Capital Intensity Ratio, and Inventory Intensity Ratio had no effect on the Tax Avoidance, while the independent variable Profitability had a significant negative effect on Tax Avoidance.